2018
DOI: 10.1159/000486920
|View full text |Cite
|
Sign up to set email alerts
|

Key Proteins Involved in Spheroid Formation and Angiogenesis in Endothelial Cells After Long-Term Exposure to Simulated Microgravity

Abstract: Background/Aims: Cardiovascular complications are common in astronauts returning from a prolonged spaceflight. These health problems might be driven by complex modulations of gene expression and protein synthesis in endothelial cells (ECs). Studies on the influence of microgravity on phenotype, growth pattern and biological processes of ECs can help to understand these complications. Methods: We exposed ECs (EA.hy926) to a Random Positioning Machine (RPM). Proteins associated with cell structure, angiogenesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 69 publications
4
54
0
1
Order By: Relevance
“…Microgravity can induce alterations in morphology, growth, and protein biosynthesis and secretion [10], depending on the responding cell type [12]. In addition, cell cultures in µg can be performed scaffold-free to engineer three-dimensional (3D) aggregates, including multicellular spheroids (MCS), tissues, and tubular structures [13][14][15]. These organoids can be used for research in space medicine [13,16] and for testing the delivery and efficacy of drugs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Microgravity can induce alterations in morphology, growth, and protein biosynthesis and secretion [10], depending on the responding cell type [12]. In addition, cell cultures in µg can be performed scaffold-free to engineer three-dimensional (3D) aggregates, including multicellular spheroids (MCS), tissues, and tubular structures [13][14][15]. These organoids can be used for research in space medicine [13,16] and for testing the delivery and efficacy of drugs [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the interactions shown in Figure 1, it has relationships to nuclear factor kappa B [25], to connective tissue growth factor, caveolin 1, and to intercellular adhesion molecule 1. All these proteins were found in earlier studies and were considered as key proteins of spheroid formation [24,38,39]. …”
Section: Resultsmentioning
confidence: 99%
“…ICAM-1 expression was heightened in macrophage-like differentiated human U937 cells during the microgravity phase of parabolic flights and in long-term microgravity provided by a two-dimensional clinostat or during the orbital SIMBOX/Shenzhou-8 mission [32,36]. Disturbed immune function in microgravity could be a consequence of ICAM-1 modulation in the monocyte/macrophage system, which, in turn, could have a strong impact on the cells' interaction with T-lymphocytes and migration [36].…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have reported that microgravity exposure changes the morphological phenotype, cell cycle, and cell adhesion, and has an impact on cell survival that is highly dependent upon the cell type, as well as on the duration of exposure [30,31]. Long-term RPM exposure of human endothelial cells induced the formation of three-dimensional tubular structures and spheroids [32]. Previous reports have shown that simulated microgravity induced partial arrest in the G2/M-phase of the MCF-7 cells and normal murine vascular smooth muscle cells, and also slowed down the cell cycle progression of myoblasts [33].…”
Section: Discussionmentioning
confidence: 99%